Student Satisfaction and Continuance Intention of E-learning System: University Student Perspective - Heru Wijayanto Aripradono; Surya Tjahyadi; Winson Kennedy (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
The development of technology has also had an impact on changes in the digitalization of the world of education, which we know as online learning. Therefore, this study aims to examine the factors that influence student satisfaction and continuance intention in using the LMS-type e-learning system. This research uses ECM as model and quantitative approach by collecting questionnaires from 443 students in Batam City who come from different universities. After the questionnaire was collected, the research hypothesis variables were tested using SEM-PLS. The results of this study found that various indicators of interactivity, course content, and design quality positively significantly affect perceived usefulness, confirmation, and satisfaction, which then affects students continuance intention to continue to use the e-learning system to support the learning process. This research shows that students in Batam are satisfied and want to continue using the e-learning system as their learning support with interactivity and adequate course content and design quality. Even so, the development of e-learning systems must still be carried out in line with technological developments, and students need to maximize the results, satisfaction, and continuance of their intention towards the use of e-learning systems.